2012
DOI: 10.4415/ann_12_04_11
|View full text |Cite
|
Sign up to set email alerts
|

The importance of waterborne disease outbreak surveillance in the United States

Abstract: Abstract. Analyses of the causes of disease outbreaks associated with contaminated drinking water in the United States have helped inform prevention efforts at the national, state, and local levels. This article describes the changing nature of disease outbreaks in public water systems during and discusses the importance of a collaborative waterborne outbreak surveillance system established in 1971. Increasing reports of outbreaks throughout the early 1980s emphasized that microbial contaminants remained a he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Disease outbreaks due to contaminated groundwater are, therefore, of great concern. In the last few decades, multiple disease outbreaks across the U.S. and Europe have been shown to have had their origin in contaminated groundwater, but it is difficult to identify specific risks due to a substantial lack of data. It can be assumed that many cases of water-associated infections go undocumented in developing countries as well as in affluent nations . Furthermore, while health risks associated with surface water contamination have been decreasing since the end of last century, this is not the case for groundwater …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease outbreaks due to contaminated groundwater are, therefore, of great concern. In the last few decades, multiple disease outbreaks across the U.S. and Europe have been shown to have had their origin in contaminated groundwater, but it is difficult to identify specific risks due to a substantial lack of data. It can be assumed that many cases of water-associated infections go undocumented in developing countries as well as in affluent nations . Furthermore, while health risks associated with surface water contamination have been decreasing since the end of last century, this is not the case for groundwater …”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, while health risks associated with surface water contamination have been decreasing since the end of last century, this is not the case for groundwater. 8 One economically advantageous treatment option to reduce the concentration of pathogens in groundwater is to ensure sufficient transport times through the porous media in question. In order to determine the pathogen removal rates in an aquifer, tracer tests with surrogate organisms are often performed; 9,10 however, field tracer tests may require special permits and are time-consuming, expensive, and site-specific.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Chicago, United States, 41 out of 160 samples were positive for Legionella from 12 of 36 recreational centers. 25 North Carolina recently faced an outbreak of LD among the people who attended the NC Mountain State Fair held in 2019. The investigation found that the outbreak of LD was caused by exposure to Legionella in aerosolized water from a hot tub that was kept for display during the fair.…”
Section: Discussionmentioning
confidence: 99%
“…2 Since the prevalence of infections caused by the genus Legionella is high in developed countries, strict surveillance systems are in place to monitor and control any outbreaks. 25,26 The exact incidence of legionellosis worldwide is unknown because of differences in national policies in reporting such cases and due to the inadequacy of knowledge pertaining to isolation and identification of the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Many incidences of waterborne diseases can be associated with contamination of surface water and groundwater due to failing on‐site domestic wastewater treatment systems (DWTSs), spreading of agricultural fecal matter (i.e., manure) and other farming activities in rural and less urbanized areas (Fetter, 2001 ; WHO, 2003 ). Despite a decrease in recent decades in waterborne disease outbreak risks related to municipal water supply sources, no corresponding decrease in disease outbreak risks for untreated or inadequately treated groundwater has been observed on the basis of outbreak reports (Craun, 2012 ). Hence, microbial pathogenic contamination of aquifers remains an ongoing, globally important, water quality problem (Ashbolt, 2004 ; Nguyen et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%